2017
DOI: 10.1016/j.celrep.2017.05.084
|View full text |Cite
|
Sign up to set email alerts
|

NOD2 Suppresses Colorectal Tumorigenesis via Downregulation of the TLR Pathways

Abstract: SUMMARY Although NOD2 is the major inflammatory bowel disease susceptibility gene, its role in colorectal tumorigenesis is poorly defined. Here, we show that Nod2-deficient mice are highly susceptible to experimental colorectal tumorigenesis independent of gut microbial dysbiosis. Interestingly, the expression of inflammatory genes and the activation of inflammatory pathways including NF-κB, ERK, and STAT3 are significantly higher in Nod2−/− mouse colons during colitis and colorectal tumorigenesis, but not at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 57 publications
1
93
0
Order By: Relevance
“…33 Also NOD2 was reported to suppress colorectal tumorigenesis via down-regulating the TLR pathways, by induction of IRF4. 34 Yet none of the articles shed light upon the mechanism of NOD2's down-regulation effect.…”
Section: Discussionmentioning
confidence: 99%
“…33 Also NOD2 was reported to suppress colorectal tumorigenesis via down-regulating the TLR pathways, by induction of IRF4. 34 Yet none of the articles shed light upon the mechanism of NOD2's down-regulation effect.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Watanabe et al., splenocytes from NOD2 –/– mice, as compared to wild‐type splenocytes, produced more IL‐12 and IL‐18 in response to agonists of TLR2 but not of several other TLRs (whereas TLR‐induced TNF and IL‐10 production was not affected) . In a study by Udden et al., bone marrow‐derived macrophages and DCs from NOD2 –/– mice showed enhanced NF‐κB and MAPK activation along with elevated IL‐1β, IL‐6, and TNF mRNA expression upon LPS and poly‐I:C stimulation in vitro . However, in Crohn's disease patients homozygous for NOD2 null mutations, most studies report unaffected responses to TLR agonists in PBMC …”
Section: Descriptive Data On Nod‐tlr Interactionsmentioning
confidence: 99%
“…Studies describing inhibitory effects of MDP on TLR‐induced responses also fall into the transcriptional cross‐regulation category, because MDP has been shown to augment expression of negative regulators of TLR signaling such as IRAK‐M or IRF4 …”
Section: Mechanisms Of Nod‐tlr Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Udden et al recently demonstrated that NOD2 negatively regulates TLR/NF-κB signaling to suppress tumorigenesis (18*). Cohousing and microbiota transfer experiments suggest that the microbiota enhances colitis but appears not to be the major driver of the increased CRC susceptibility observed in Nod2 -/- mice compared to WT mice (18*). Mechanistically, NOD2 induces IRF4 which interacts with MYD88 and TRAF6 to suppress TLR/NF-κB signaling in myeloid cells (18*).…”
Section: Innate Sensors and Immune Signalingmentioning
confidence: 99%